Potential of Rural Biogas from Cow Fecal Waste and Implementation of Sociopreneurship-Based Energy-Independent Village - Syeftyan Muhammad Ali Hamami; M. Nizam Zulfi Zakaria; Ahmad Fariduddin Aththar (Universitas Brawijaya, 2022)
The energy crisis is a crucial problem as evidenced by data from Indonesia Outlook Energy which states that 88% of the total electricity is comes from fossil fuels whose reserves continue to decline. This encourages the government to suppress the use of fossil fuels and look for alternative renewable energy sources. Indonesia has a promising livestock sector but its utilization is still not optimal. One of those is cow fecal waste that generally has been used as potential biogas. It is necessary to have a program to optimize the utilization of cow feces as biogas in villages and integrate it with the sociopreneurship-based energy-concept independent village. The purpose of this paper is to analyze the potential of cow fecal waste as an alternative energy source based on community conditions, analyze the implementation of energy-concept independent village, sociopreneurship basis and the financial aspects of the program, as well as implementation strategy and sustainability of the program to achieve SDGs target. The research was conducted using data collection methods, data processing, and data analysis. Energy-independent village is able to occupy its energy consumption by optimizing the potential from indigenous product. This program integrates a supporting system consisting of a Special Team, cow farmers, ROFES (House of Feces), and GUBAS (Village Biogas Warehouse). The implementation of this research program includes pre-production, production, and post-production stages. This program is expected to be able to contribute to fulfill the energy needs of the village by optimizing cow fecal waste and supporting the SDG's targets.